A review of the importance of immune responses in luminal B breast cancer - Nelson, Delia; Clark, B.; Munyard, K.; Williams, V.; Groth, David; Gill, J.; Preston, H.; Chan, A. (Landes Bioscience, 2017)
© 2017 Taylor & Francis Group, LLC. Historically, the immune environment was not considered an important target for breast cancer treatment. However, the association of lymphocytic infiltrates in triple negative and HER-2 over-amplified breast cancer subtypes with better outcomes, has provoked interest in evaluating the role of the immune system in the luminal B subtype that accounts for 39% of breast cancers and has a poor patient prognosis. It is unknown which immunosuppressive cell types or molecules (e.g., checkpoint molecules) are relevant, or where measurement is most informative. We hypothesize that a profound immunosuppressive tumor and/or lymph node milieu is prognostic and impacts on responses to therapies.